2018
DOI: 10.1016/j.smallrumres.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial or total replacement of corn cracked grain with high concentrations of crude glycerin on rumen metabolism of crossbred sheep

Abstract: Crude glycerin, a by-product of the biodiesel industry, has been used as a strategic ingredient in intensive ruminant production systems, mainly in substitution of starch-rich ingredients. The present study was performed to evaluate the effects of the inclusion of up to 30% of crude glycerin in diets for feedlot sheep, on ruminal parameters, such as pH, NH 3-N and volatile fatty acids concentrations, in situ degradability, as well as in vitro greenhouse gas production and in vitro digestibility. Eight ruminall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…In addition, Saleem et al [26] reported enhanced fiber digestion with supplemental glycerin. Furthermore, van Cleef et al [6] concluded that the effective degradation and the in vitro DM digestibility of diets were improved when crossbred sheep were fed a partial or total replacement of corn cracked grain with crude glycerin at high doses. However, Abu Ghazaleh et al [4] noted that glycerin addition decreased in vitro NDF digestion due to the decreasing bacterial counts associated with feed digestibility.…”
Section: In Vitro Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Saleem et al [26] reported enhanced fiber digestion with supplemental glycerin. Furthermore, van Cleef et al [6] concluded that the effective degradation and the in vitro DM digestibility of diets were improved when crossbred sheep were fed a partial or total replacement of corn cracked grain with crude glycerin at high doses. However, Abu Ghazaleh et al [4] noted that glycerin addition decreased in vitro NDF digestion due to the decreasing bacterial counts associated with feed digestibility.…”
Section: In Vitro Digestibilitymentioning
confidence: 99%
“…This likely occurred because crude glycerin, which is similar to a fermentable carbohydrate source, underwent ruminal fermentation to C3. Van Cleef et al [6] noted that the change in the relative C3 ratio was probably due to the fermentation properties of crude glycerin, which is fermented mainly by Selenomonas bacteria and mostly used by ruminants during the first 4-6 h after digestion. Almeida et al [29] found the higher ratio of crude glycerin (~43%) is quickly absorbed by the rumen wall, whereas 25% to 45% is converted to C2 and C3 by an alternative fermentative route (via succinate) and does not produce lactic acid, thus advancing the rumen's maturation and enhancing diet use.…”
Section: Concentration Total Volatile Fatty Acid and Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several in vivo and in situ studies have reported increases in total VFA production [34,[41][42][43]. Differently, other authors evaluating the increasing inclusions of crude glycerin in diets for crossbreed lambs (up to 30% DM, in [28,44]) and Nellore bulls (up to 30% DM, [36]) observed a linear decrease in total VFA with no changes in propionic acid concentration. However, a pronounced reduction in acetic acid concentration was observed.…”
Section: Ruminal Digestion and Fermentation Of Crude Glycerinmentioning
confidence: 99%
“…Most of them are related to the end products of glycerol fermentation and its effects on ruminal microorganisms. However, promising results regarding growth performance and feed efficiency have been reported for inclusion up to 20% of crude glycerin in diets for feedlot lambs [26][27][28]. Therefore, this chapter discusses important aspects of different inclusions and associations of crude glycerin, including glycerol digestibility and metabolism and practical applications in sheep nutrition and production.…”
Section: Introductionmentioning
confidence: 99%